Pengembangan Pariwisata Dan Dampak Sosial Ekonomi Di Bandar Lampung - Muhammad Luthfi (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2013)
Tourism is an activity trip or part of these activities are voluntary and temporary objectsand to enjoy the tourist attraction of tourism sector is a significant source of foreign exchange and thepercentage contribution to the local treasury , which is widely also a source of foreign exchange. Thecapital city of Bandar Lampung province with an area of 197.22 km2 comprised of 13 districts and 98villages . This study aims to determine the development of tourism in the economic and social impactof Bandar Lampung . The results showed a relationship attraction development and socio-economicimpact is low at 15.70 % means that tourism development does not have an impact on the socioeconomicsituation in Bandar Lampung . The role of local governments is needed in this case in theform of policy and as a mediator between citizens about the location of the employer attractionattractionKeywords; economic and social attraction